Efficacy and safety of 20% azelaic acid cream for papulo-pustular acne vulgaris - Reznichenko, N. Yu.; Reznichenko, Yu. G.; Reznichenko, G. I.; Veretelnyk, K. O.; Резніченко, Наталія Юріївна; Резніченко, Юрій Григорович; Резніченко, Галина Іванівна; Веретельник, Ксенія Олександрівна (My University, 2021)
Purpose of the study. To determine the safety and efficacy of 20% azelaic acid cream in the treatment of patients with papulopustular acne vulgaris. Materials and methods. 65 patients with acne vulgaris were examined. The control group consisted of 30 healthy individuals. Acne severity was evaluated according to G. Michaelsson et al. scale, Cook’s scale, absolute number of papules and pustules. Assessment of quality of life was performed. Facial skin microbiocenosis was assessed. All patients with acne vulgaris applied 20% azelaic acid cream during 15 ± 2 days. Results and discussion. The use of 20% azelaic acid cream contributed to the rapid regression of inflammatory acne. After 10 days of treatment, the number of papulopustular elements decreased in 3 times. After 10 days of therapy acne score according to G. Michaelsson et al. decreased in 1,5 times and after 15 days of treatment – in 1,9 times. After 10 days of therapy the acne score on the Cook’s scale decreased in 1,4 times. At the end of the study the acne score on the Cook’s scale was 2,4 points. There was a significant decrease in the total number of bacteria, the number of coagulase-positive staphylococci, quantity of Propionibacterium acnes on facial skin in 15 days after the start of therapy. A significant difference in the average value of the DLQI was fixed before (18,9 ± 0,31) and at the end (8,1 ± 0,54) of treatment. Conclusions. The high effectiveness of 20% azelaic acid cream in treatment of papulopustular acne vulgaris was proved. 20% azelaic acid cream provides a rapid regression of inflammatory forms of acne, reduction of total quantity of bacteria and Propionbacterium acnes on skin.
Ефективність та безпека застосування 20% крему азелаїнової кислоти для лікування папуло-пустульозної форми вульгарних акне
Keywords: acne vulgaris; treatment; azelaic acid; акне вульгарні; лікування; азелаїнова кислота